PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS POWTOON PADA MATA PELAJARAN TEKNIK PENGUKURAN TANAH DI SMK NEGERI 5 BANDUNG - Muhammad Faiq Sani Nugraha; Sudjani Sudjani; Dedi Purwanto (Universitas Pendidikan Indonesia (UPI), 2022)
Learning media and learning methods are one aspect that can be developed by teachers to achieve effective and efficient learning. Animated video learning media is the most possible media to be used in learning activities during the pandemic covid-19 because animated video learning media allows students to study independently at home and does not require direct interaction. The research method used in this research is research and development. This research was carried out through six stages of research, namely the collection of potentials and problems; data collection; video product planning; product validation by 2 media experts, 1 material expert, and 1 linguist; product revision; and limited product trials to 61 X KGSP students at SMK Negeri 5 Bandung. From the validation stage, the results obtained that the media was suitable for use without revision after 2 validation tests to media experts and material experts, as well as 1 validation test to linguists and obtained the results of the percentage of student responses of 77.79% with positive criteria so that it can be concluded that the product- based animated video learning media is Powtoon able to assist students in carrying out the learning process in the subject of Soil Measurement Techniques.